2014
DOI: 10.1007/978-3-319-09614-8_17
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, Carcinoembryonic Antigen Processing and Colorectal Liver Metastases

Abstract: It is well established that alcohol consumption is related to the development of alcoholic liver disease. Additionally, it is appreciated that other major health issues are associated with alcohol abuse, including colorectal cancer (CRC) and its metastatic growth to the liver. Although a correlation exists between alcohol use and the development of diseases, the search continues for a better understanding of specific mechanisms. Concerning the role of alcohol in CRC liver metastases, recent research is aimed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The role of CEA in metastasis is not fully characterized but implicated as a prometastatic adhesion and signaling molecule that interacts with cells in the hepatic microenvironment [ 52 , 53 ]. Moreover, the prometastatic effects of CEA are enhanced in the setting of pre-existing liver disease including alcoholic [ 5 , 54 ] and nonalcoholic liver disease [ 55 , 56 ]. Most recently, it was reported that NAFLD and CEA expression are associated with an increased incidence of liver metastasis in CRC patients [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of CEA in metastasis is not fully characterized but implicated as a prometastatic adhesion and signaling molecule that interacts with cells in the hepatic microenvironment [ 52 , 53 ]. Moreover, the prometastatic effects of CEA are enhanced in the setting of pre-existing liver disease including alcoholic [ 5 , 54 ] and nonalcoholic liver disease [ 55 , 56 ]. Most recently, it was reported that NAFLD and CEA expression are associated with an increased incidence of liver metastasis in CRC patients [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…non-alcoholic fatty liver disease (nAfLd) and alcoholic liver disease are major health issues associated with tumor cell metastasis to the liver (28). According to previous studies, high alcohol intake is associated with CRLM (29,30).…”
Section: Pri-metastatic Nichementioning
confidence: 99%
“…According to previous studies, high alcohol intake is associated with CRLM (29,30). Both KCs and hepatocytes are affected by alcohol, and high expression of lipopolysaccharides and pro-inflammatory cytokines, such as TNFα and IL-1β changes the hepatic niche and CRC metastasis (28). nAfLd has been used to demonstrate the higher metastatic burden in steatotic livers compared with that in normal livers.…”
Section: Pri-metastatic Nichementioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol consumption is very common in developed countries and has been confirmed to be an important risk factor for CRC, and particularly strong associations have been obtained with chronic and moderate to heavy alcohol intake [4]. Moreover, increasing numbers of epidemiological studies have revealed that alcohol consumption is also closely related to metastasis in patients with CRC, and this association was identified as the primary reason for the poor outcomes observed in these patients [8,9]. Due to the difficulty in detecting CRC at an early stage [10], it was conceivable to conclude that most CRC patients would not change their lifestyles until obvious symptoms and/or signs were detected.…”
Section: Introductionmentioning
confidence: 99%